Thresh + Hold - Dantas, Paulo (2024)
Thresh + Hold is a multimodal report on the generative distance between experiences of loss as they relate to sound: losses of quality, memory, presence, time, labor, resources, intimacy, and voice. It works by juxtaposing and overlaying different kinds of loss across media formats: cyanotypes of fieldwork photos that make visible the loss of light as it imprints on the photographic medium; interlocking collages of absent sounds punctuating time spent and time lost in the field; and fragments of conversations that evoke thresholds of (mis)understanding, (mis)hearing, and (mis)communicating. By bringing together our materials, we commit to trust through tinkering and to tinkering with trust. The project received funding from the Dutch Research Council (NWO).
FRIS
1
Keywords: Music, Thought and Technology